(μ2-Adipato-κ4 O,O′:O′′,O′′′)bis[aqua(benzene-1,2-diamine-κ2 N,N′)chloridocadmium]: crystal structure and Hirshfeld surface analysis - Rahman, W.S.K.A.; Ahmad, J.; Halim, S.N.A.; Jotani, M.M.; Tiekink, E.R.T. (International Union of Crystallography, 2017)
The full molecule of the binuclear title compound, [Cd2Cl2(C6H8O4)(C6H8N2)2(H2O)2], is generated by the application of a centre of inversion located at the middle of the central CH2-CH2 bond of the adipate dianion; the latter chelates a CdII atom at each end. Along with two carboxylate-O atoms, the CdII ion is coordinated by the two N atoms of the chelating benzene-1,2-diamine ligand, a Cl- anion and an aqua ligand to define a distorted octahedral CdClN2O3 coordination geometry with the monodentate ligands being mutually cis. The disparity in the Cd-N bond lengths is related to the relative trans effect exerted by the Cd-O bonds formed by the carboxylate-O and aqua-O atoms. The packing features water-O-H⋯O(carboxylate) and benzene-1,2-diamine-N-H⋯Cl hydrogen bonds, leading to layers that stack along the a-axis direction. The lack of directional interactions between the layers is confirmed by a Hirshfeld surface analysis.